PENGENALAN LAMBANG BILANGAN MELALUI PERMAINAN ULAR TANGGA PADA PENDIDIKAN ANAK USIA DINI - Niken Novirasiwi, - (2022)
ABSTRAK Mengenal konsep bilangan merupakan bagian dari kemampuan kognitif anak. Kemampuan mengenal lambang bilangan pada anak sangat penting dikembangkan guna memperoleh kesiapan dalam mengikuti pembelajaran khususnya dalam penguasaan konsep matematika. Kenyataannya, di lapangan ditemukan bahwa pengenalan lambang bilangan pada anak usia dini tergolong cukup rendah. Maka dari itu dilaksanakan penelitian dengan tujuan untuk mengetahui perbedaan kemampuan mengenal lambang bilangan anak usia 4-5 tahun sebelum dan sesudah penerapan permainan ular tangga. Metode dalam penelitian ini adalah pendekatan kuantitatif pre-eksperimen dengan Design One Group Pre-test Post-test. Teknik pengolahan data dalam penelitian ini, adalah: 1) Analisis data Statistik Deskriptif; 2) Tabel; 3) Rata-rata hitung; 4) Standar Deviasi; 5) Analisis Statistik Inferensial; 6) Uji normalitas; 7) Uji homogenitas; 8) Uji t; 9) Uji n-gain. Berdasarkan hasil pengolahan data, dapat disimpulkan bahwa terdapat pengaruh penggunaan permainan ular tangga terhadap kemampuan mengenal lambang bilangan pada anak usia 4-5 tahun, yang dibuktikan dengan nilai rata-rata pretest sebesar 1.52 meningkat menjadi 3,25 setelah treatment menggunakan permainan ular tangga. Hasil ini diperkuat dengan N-Gain Score sebesar 0,8 > 0,7, yang termasuk dalam kategori tafsiran tinggi. Jika dipresentasikan sebesar 73.61%. ----- ABSTRACT Recognizing the concept of numbers is part of children's cognitive abilities. The ability to recognize number symbols in children is very important to develop in order to obtain readiness in participating in learning, especially in mastering mathematical concepts. In fact, in the field it was found that the recognition of number symbols in early childhood is quite low. Therefore, the research was carried out with the aim of knowing the ability to recognize number symbols of children aged 4-5 years before the application of the snake and ladder game, to determine the effect of the snake and ladder game to introduce number symbols to children aged 4-5 years. The method in this study is a quantitative pre-experimental approach with Design One Group Pre-test Post-test. The data processing techniques in this study are: 1) Descriptive statistical data analysis; 2) Tables; 3) Calculated average; 4) Standard Deviation; 5) Inferential Statistical Analysis; 6) Normality test; 7) Homogeneity test; 8) t test; 9) n-gain test. Based on the results of data processing, it can be concluded that there is an effect of using the snake and ladder game on the ability to recognize number symbols in children aged 4-5 years, as evidenced by the average pretest score of 1.52 which increased to 3.25 after treatment using the snake and ladder game. This result is reinforced by 2) Tables; 3) Calculated average; 4) Standard Deviation; 5) Inferential Statistical Analysis; 6) Normality test; 7) Homogeneity test; 8) t test; 9) n-gain test. Based on the results of data processing, it can be concluded that there is an effect of using the snake and ladder game on the ability to recognize number symbols in children aged 4-5 years, as evidenced by the average pretest score of 1.52 which increased to 3.25 after treatment using the snake and ladder game. This result is reinforced by 2) Tables; 3) Calculated average; 4) Standard Deviation; 5) Inferential Statistical Analysis; 6) Normality test; 7) Homogeneity test; 8) t test; 9) n-gain test. Based on the results of data processing, it can be concluded that there is an effect of using the snake and ladder game on the ability to recognize number symbols in children aged 4-5 years, as evidenced by the average pretest score of 1.52 which increased to 3.25 after treatment using the snake and ladder game. This result is reinforced by as evidenced by the average pretest score of 1.52 which increased to 3.25 after treatment using the snake and ladder game. This result is reinforced by as evidenced by the average pretest score of 1.52 which increased to 3.25 after treatment using the snake and ladder game. This result is reinforced by N-Gain Score of 0.8 > 0.7, which is included in the category of high interpretation. If presented by 73.61%.